2007
DOI: 10.3171/ped.2007.106.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Chiari-like tonsillar herniation associated with intracranial hypotension in Marfan syndrome

Abstract: The authors describe the case of a 12-year-old girl with Marfan syndrome, sacral dural ectasia, and tonsillar herniation, who presented with headache. Initially, it was hypothesized that the headaches were secondary to the tonsillar herniation, and the patient consequently underwent surgical decompression of the foramen magnum. Postoperatively, the patient's condition did not improve, and additional magnetic resonance (MR) imaging demonstrated evidence of a cerebrospinal fluid (CSF) leak at the level of the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…There is only one case report in the literature that links spontaneous CSF leak complicated by tonsillar herniation in a Marfan patient [17]. This complication was also seen in our patient.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There is only one case report in the literature that links spontaneous CSF leak complicated by tonsillar herniation in a Marfan patient [17]. This complication was also seen in our patient.…”
Section: Discussionsupporting
confidence: 75%
“…Tonsillar herniation is considered a part of the SIH complex and has been labeled as "acquired Chiari - Malformation I (CM-I)" [17]. Lack of awareness or erroneous diagnoses has been reported to lead to unnecessary surgical intervention such as suboccipital craniectomy for posterior fossa decompression in an attempt to treat intractable headaches thought to be caused by tonsillar herniation; only later was it realized that the real cause of headaches was SIH secondary to CSF leaks [17].…”
Section: Discussionmentioning
confidence: 99%
“…These include twin studies [1], [10], [11], [12], [13], [14], [15], [16], familial clustering [10], [14], [15], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], and co-segregation with known genetic syndromes or conditions commonly found as part of a genetic syndrome, including Ehlers-Danlos syndrome [9], [31], [32], [33], Marfan syndrome [9], [34], [35], [36], Klippel-Feil syndrome [23], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], growth hormone deficiency [45], [46], [49], [50], [51], [52], [53], [54], [55], craniosynostosis [56], [57], and Neurofibromatosis type I [58], [59]. Furthermore, in a study conducted by Milhorat and colleagues, it was reported that out of a cohort of 364 symptomatic patients, 43 (12%) had at least one close relative with CMI with or without syringomyelia or idi...…”
Section: Introductionmentioning
confidence: 99%
“…In children, adolescents, and young adults, these headaches are often the only apparent symptom of dural ectasia and are generally attributed to intracranial hypotension secondary to CSF leaks, causing traction on pain-sensitive structures like cranial nerves, dura, and meninges. [15][16][17][18][19][20][21][22][23][24] Pain in the lower back, the anogenital region and the legs, as well as muscular weakness and paresthesia of the lower extremities have been reported as being associated with dural ectasia and arachnoid cysts, 13,14 typically indicating lumbosacral nerve root compression. 10,25 A potential cause for the formation of dural ectasia and arachnoidal cysts in Marfan syndrome and other connective tissue disorders might be a progressive dural weakness due to hydrostatically induced higher intrathecal pressures and the propagation of CSF pulsations.…”
Section: Discussionmentioning
confidence: 99%